2016
DOI: 10.2135/cropsci2014.11.0793
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water Regime Affecting Correlation of Carbon Isotope Discrimination with Yield and Water‐Use Efficiency of Winter Wheat

Abstract: Improving crop water‐use efficiency (WUE) is critical in securing food production under arid and semiarid regions, but a quick and accurate method for quantifying crop WUE is lacking. A field study on winter wheat (Triticum aestivum L.) was conducted under six irrigation regimes in two growing seasons (2011–2012 and 2012–2013) to determine the sampling time and the condition of soil moisture on the relationship of C isotope discrimination (Δ13C; measured by flag leaves, other leaves, and kernel) with grain yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…For both experimental years, grain CID demonstrated strong linear relationships with grain yield; this finding agrees with the results reported from the studies conducted by Lopes and Reynolds (2010) and Araus et al (2008). Moreover, leaf CID decreased with increasing drought stress (Table 3), agreeing with the results of Wang et al (2016). At anthesis, leaf and grain CID exhibited strong positive relationships with RLWC and strong negative relationships with leaf temperature for both experimental years (Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…For both experimental years, grain CID demonstrated strong linear relationships with grain yield; this finding agrees with the results reported from the studies conducted by Lopes and Reynolds (2010) and Araus et al (2008). Moreover, leaf CID decreased with increasing drought stress (Table 3), agreeing with the results of Wang et al (2016). At anthesis, leaf and grain CID exhibited strong positive relationships with RLWC and strong negative relationships with leaf temperature for both experimental years (Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…However, there is inconsistency in the relationship between CID and WUE when scaling up the relation from WUE l to the canopy level, namely, grain yield or WUE g . For example, positive relationships are reported in Condon et al (1987), Monneveux et al (2005), and Wang et al (2013Wang et al ( , 2016, whereas negative relationships are reported in Condon et al (2004). Condon et al (2004) and Foulkes et al (2016) show little agreement in their studies.…”
mentioning
confidence: 94%
“…Leaf-based studies are relatively convenient to conduct, as it is easy to readily collect leaf samples in the field and many studies use CID to investigate WUE (Zhao, 2004;Moghaddam et al, 2013;Wang et al, 2013Wang et al, , 2016Raimanová et al, 2016). Other studies explore the genetic controls on WUE and CID (Teulat et al, 2002;Rebetzke et al, 2008;Xu et al, 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations